2014
DOI: 10.1111/ijac.12312
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Spectroscopic Properties of δ‐Y2Si2O7 Nanopowders Activated with Nd3+ Ions

Abstract: Phosphors of δ‐Y2Si2O7 doped with Nd3+ ions were prepared in the SiO2–Y2O3 binary systems using the solgel technique. Nano‐sized crystalline phosphor powders were obtained by annealing the dried gels at 1480°C. The average grain sizes of the NYS1, NYS2, NYS3, and NYS4, powders were estimated to be 44.1, 41.3, 48.1, and 53.2 nm from the grain size distribution curves, respectively, and these results were confirmed by transmission electron microscope measurements. The spectroscopic properties of the powders were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Therefore, most rare‐earth elements are generally preferred for phosphor and laser materials production as dopants. Potential application fields of rare earth‐doped phosphor materials include solar panels, field‐emission displays (FEDs), scintillation, cathode‐ray tubes (CRTs), vacuum fluorescent displays (VFDs) and white light‐emitting diodes (W‐LEDs) . White LEDs are generally considered to be the new generation light sources, which are able to replace the fluorescent lamps, because of their excellent features in terms of low energy consumption, fast response, mercury free, high efficiency, low voltage adjustability, environmental‐friendly and energy‐saving devices.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, most rare‐earth elements are generally preferred for phosphor and laser materials production as dopants. Potential application fields of rare earth‐doped phosphor materials include solar panels, field‐emission displays (FEDs), scintillation, cathode‐ray tubes (CRTs), vacuum fluorescent displays (VFDs) and white light‐emitting diodes (W‐LEDs) . White LEDs are generally considered to be the new generation light sources, which are able to replace the fluorescent lamps, because of their excellent features in terms of low energy consumption, fast response, mercury free, high efficiency, low voltage adjustability, environmental‐friendly and energy‐saving devices.…”
Section: Introductionmentioning
confidence: 99%
“…Although, various rare earth-activated yttrium orthosilicates have been studied a lot [17][18][19][20][21][22][23][24][25][26][27][28] [25].…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth elements (RE) doped, co-doped and tridoped Y2Si2O7 are crucial nanophosphors for lasers, light emitting diodes (LED), white LED and plasma display panel applications [13][14][15][16]. Although, various rare earth-activated yttrium orthosilicates have been studied a lot [17][18][19][20][21][22][23][24][25][26][27][28], there have been a few studies reported on the Er 3+ : Y2Si2O7. Diaz et al analyzed the luminescence properties of Y2Si2O7 : Dy phosphors prepared by a new pressureless hydrothermal route.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…δ -Y 2 Si 2 O 7 crystallizes into an orthorhombic structure with the Pna 21 space group and assigns unique crystallographic sites to Y 3+ ions both with coordination number seven [4]. However, researchers focused on the optical spectroscopy properties of yttrium disilicates (Y 2 Si 2 O 7 ) [5][6][7][8][9][10][11][12][13] and no extensive study on the magnetic properties of yttrium disilicates when activated with neodymium has been observed in the literature. In this study, we first report on the magnetic properties of nanocrystalline α , γ , and δ polymorphs of yttrium disilicate (Y 2 Si 2 O 7 ) prepared by the sol-gel method.…”
Section: Introductionmentioning
confidence: 99%